Nursing student peer mentorship: a review of the literature. Issue 1 (1st January 2017) - Rohatinsky, Noelle; Harding, Katie; Carriere, Terra
Abstract: The benefits of peer student mentorship programs are making them increasingly popular in nursing education. This manuscript reviews and synthesizes 20 articles outlining key elements, outcomes, and barriers of nursing student peer mentorship programs to allow educators to create mentorship programs that meet the needs of their students, faculty, and institution in order to foster professional development and socialization among students. Peer mentorship was used to develop students' skills in four main areas: Clinical (psychomotor and professional nursing skills), laboratory (psychomotor skills), socialization (to the post-secondary education system), and academia (study skills to enhance academic success). Mentorships were mutually beneficial for first year and upper year students in all settings. Ultimately, the skills attained through mentorships can be transferred to students' academic studies and future careers.